2022
DOI: 10.1039/d2nj00079b
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus–carbon covalent bond induced kinetics modulation of vanadium diphosphide for room- and high-temperature sodium-ion batteries

Abstract: Metal phosphides are of great interest in sodium-ion batteries due to their high capacity in theory and suitable redox potential. However, the large bulk expansion and sluggish diffusion kinetics greatly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Because sodium (Na) and lithium (Li) have similar physiochemical properties and are both inexpensive and widely available, sodium-ion batteries (SIBs) have attracted considerable interest for use in energy storage applications. , This emphasizes the search for superb anode materials with an extended cyclic life and improved rate performance for SIBs. Transition-metal phosphides (TMPs) are seeking attention as an anode material because of their environmental as well as electrochemical characteristics, such as larger theoretical capacity, superior electrical conductivity, and lower voltage plateau compared with selenides, sulfides, and metal oxides. Previously, various transition metals, including ZnP 2 , VP 2 , CoP, MoP, Ni 2 P, Cu 3 P, Sn 4 P 3 , and GeP, have demonstrated good electrochemical performances within SIBs. , Notwithstanding these developments, there is still scope for improvement in the electrode’s structural integrity and reversible capacity throughout repeated cycling, particularly at a higher current density. In recent years, TMPs with distinct morphologies, such as nanoparticles, nanowires, nanotubes, nanofibers, and hollow spheres, have been synthesized using various methods, including ball milling, metal–organic framework (MOF), , electrochemical depositions, solvothermal, carbothermal reduction, and electrospinning .…”
Section: Introductionmentioning
confidence: 99%
“…Because sodium (Na) and lithium (Li) have similar physiochemical properties and are both inexpensive and widely available, sodium-ion batteries (SIBs) have attracted considerable interest for use in energy storage applications. , This emphasizes the search for superb anode materials with an extended cyclic life and improved rate performance for SIBs. Transition-metal phosphides (TMPs) are seeking attention as an anode material because of their environmental as well as electrochemical characteristics, such as larger theoretical capacity, superior electrical conductivity, and lower voltage plateau compared with selenides, sulfides, and metal oxides. Previously, various transition metals, including ZnP 2 , VP 2 , CoP, MoP, Ni 2 P, Cu 3 P, Sn 4 P 3 , and GeP, have demonstrated good electrochemical performances within SIBs. , Notwithstanding these developments, there is still scope for improvement in the electrode’s structural integrity and reversible capacity throughout repeated cycling, particularly at a higher current density. In recent years, TMPs with distinct morphologies, such as nanoparticles, nanowires, nanotubes, nanofibers, and hollow spheres, have been synthesized using various methods, including ball milling, metal–organic framework (MOF), , electrochemical depositions, solvothermal, carbothermal reduction, and electrospinning .…”
Section: Introductionmentioning
confidence: 99%
“…[243] Copyright 2022, The Royal Society of Chemistry and the Centre National de la Recherche Scientifique. temperature of 60 °C, [251] as well as good multiplicity adaptability and structural stability (Figure 20h,i). The carbon matrix not only offers a quick channel for charge transfer but also reduces the volume expansion because of its softness.…”
Section: External Structure Modificationmentioning
confidence: 98%
“…[ 250 ] However, its serious volume expansion and slow charge transfer should not be neglected as well. It has been found that the use of composite can alleviate these problems, such as diphosphide/phosphorus/carbon (VP 2 /3P/C) composite anode can provide high capacity at high temperature of 60 °C, [ 251 ] as well as good multiplicity adaptability and structural stability (Figure 20h,i). The carbon matrix not only offers a quick channel for charge transfer but also reduces the volume expansion because of its softness.…”
Section: Explorations Of High‐temperature Sibsmentioning
confidence: 99%
“…Due to the large volume expansion and the severe specific capacity reduction of VP 2 , coupling it with conductive carbon-based materials can further improve the electronic conductivity and the stability of composite electrodes and mitigate the huge volume expansion. Ye et al synthesized VP 2 /3P/C composite with high specific capacity, [165] which can reach 550 mAh g −1 at 50 mA g −1 . Even at high temperatures of 60 °C, VP 2 /3P/C composite exhibits high capacities of 630 and 375 mAh g −1 at 50 mA g −1 and 5 A g −1 .…”
Section: V-pmentioning
confidence: 99%
“…Ye et al. synthesized VP 2 /3P/C composite with high specific capacity, [ 165 ] which can reach 550 mAh g −1 at 50 mA g −1 . Even at high temperatures of 60 °C, VP 2 /3P/C composite exhibits high capacities of 630 and 375 mAh g −1 at 50 mA g −1 and 5 A g −1 .…”
Section: Metal Phosphide In Sibsmentioning
confidence: 99%